The Role of Green Products on Buying Interest in the Culinary MSME Sector in Makassar - Advencia Desti; Mawardi, Mawardi; Usman, Ahmadi (Journal of Business Administration (JBA), 2026)
Increasing public awareness of environmental issues has affected consumer preferences, especially in choosing sustainable products. In the culinary MSME sector in Makassar, the adoption of eco-friendly products such as eco-friendly packaging and natural ingredients is still limited due to a lack of awareness, promotion, and higher cost perception. This gap highlights the importance of investigating how the attributes of eco-friendly products affect consumer purchase intent. This study aims to analyze consumer perception of green products in culinary MSMEs in the city of Makassar, consumer purchase intention of green products in culinary MSMEs in the city of Makassar, and the role of green products on consumer purchase intention in culinary MSMEs in Makassar. This study uses a quantitative approach applied with a descriptive and associative approach. Data were collected through questionnaires and interviews with 100 respondents selected by purposive sampling. Data were analyzed using SPSS 30, including validity and reliability tests, normality tests, simple linear regression, t-tests, and determination coefficients. The findings show that consumer perception of environmentally friendly products is relatively high, especially related to raw materials and production processes. Consumers' purchase intentions for environmentally friendly culinary products are also included in the high category. Furthermore, regression analysis confirms that eco-friendly products significantly affect purchase intent. These results show that the implementation of environmentally friendly product practices can strengthen consumer loyalty and support the sustainability of MSMEs in the culinary sector.